A high-crystalline carbon nitride nanomaterial and its preparation method and application

By mixing the precursor with the fluoride salt and calcining it, the problem of the synthesis of high-crystalline carbon nitride materials in the prior art requires a large amount of alkaline salt and high temperature, achieving an efficient and low-cost preparation process, and maintaining the high crystalline structure and good photocatalytic properties of the material.

CN118908157BActive Publication Date: 2025-04-01SHENZHEN INSTITUTE OF INFORMATION TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410952987.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2025-04-01
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

The method of synthesizing highly crystalline carbon nitride materials in the prior art requires a large amount of alkaline salts and high calcining temperatures, resulting in high production costs and waste of energy.

Method used

High crystalline carbon nitride nanomaterials are prepared by mixing the precursor with the fluoride salt evenly and then calcining, and using less fluoride salt and lower calcining temperature.

Benefits of technology

The preparation of high-crystalline carbon nitride nanomaterials is achieved, which reduces preparation costs, reduces energy waste, and maintains the high crystalline structure and good photocatalytic properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908157B_ABST
    Figure CN118908157B_ABST
Patent Text Reader

Abstract

The invention discloses a high-crystalline carbon nitride nanomaterial and a preparation method and application thereof, and relates to the technical field of carbon nitride materials. A method for preparing a high-crystalline carbon nitride nanomaterial comprises mixing a precursor and a fluoride salt uniformly and then calcining the mixture, washing and drying the mixture to obtain a high-crystalline carbon nitride nanomaterial; the mass ratio of the fluoride salt to the precursor is (0.01-1): 1; the calcination parameters are: a heating rate of 3-8°C / min, a holding temperature of 550-650°C, and a holding time of 2-4h. The method for preparing a high-crystalline carbon nitride nanomaterial of the invention comprises directly mixing a precursor and a fluoride salt uniformly and then calcining the mixture, and only a small amount of fluoride salt and a relatively low calcination temperature are required to prepare a high-crystalline carbon nitride nanomaterial; the preparation process is simple, the preparation cost is reduced, and energy waste is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon nitride materials, and in particular to a high-crystalline carbon nitride nanomaterial and a preparation method and application thereof. Background Art

[0002] In recent years, graphitic carbon nitride has become a promising visible light catalyst due to its simple preparation, low cost, non-toxicity, high stability, and suitable electronic band gap. However, conventional graphite phase carbon nitride has problems such as poor crystallinity, small specific surface area, slow carrier separation, and fast carrier recombination. In order to solve these problems, it has become a common strategy to improve the crystallinity of carbon nitride and ultimately improve the photocatalytic activity through the molten salt method. Generally, a mixture of carbon nitride precursors and alkaline molten salts is used to prepare carbon nitride materials with high crystallinity and long period structures, which can effectively increase the charge migration rate, reduce carrier recombination, reduce the band gap, improve light absorption efficiency, and ultimately improve photocatalytic activity.

[0003] Some studies have pointed out that the use of high melting point alkaline salts to prepare highly crystalline carbon nitride materials, such as NaCl, KSCN, etc., can effectively establish a stable reaction environment, which is conducive to slowing down the growth of grains, and finally synthesizing highly crystalline carbon nitride materials based on the heptazine ring structure. In this synthesis reaction using alkaline salts, the alkaline salt itself is mainly used as a synthesis template, so a large amount of alkaline salts and a higher calcination temperature are required to promote the synthesis of highly crystalline carbon nitride.

[0004] Therefore, the method for synthesizing highly crystalline carbon nitride in the prior art requires a large amount of alkaline salt and a high calcination temperature, which leads to high preparation cost and energy waste. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a method for preparing highly crystalline carbon nitride nanomaterials, aiming to solve the problem that the method for synthesizing highly crystalline carbon nitride in the prior art requires a large amount of alkaline salt and a high calcination temperature, thereby resulting in high preparation cost and energy waste.

[0006] In order to solve the above technical problems, the purpose of the present invention is achieved through the following technical solutions:

[0007] In one aspect, the present invention discloses a method for preparing a highly crystalline carbon nitride nanomaterial.

[0008] The precursor and the fluoride salt are uniformly mixed, calcined, washed and dried to obtain a highly crystalline carbon nitride nanomaterial;

[0009] The mass ratio of the fluoride salt to the precursor is (0.01-1):1;

[0010] The calcination parameters are: heating rate 3-8°C / min, insulation temperature 550-650°C, insulation time 2-4h.

[0011] Optionally, the precursor is selected from at least one of thiourea, melamine, dicyandiamide and urea.

[0012] Optionally, the fluoride salt is selected from at least one of NaF, LiF, and KF.

[0013] Optionally, the drying parameters are: drying temperature 50-80°C.

[0014] Optionally, the calcination is carried out under an inert gas atmosphere, and the inert gas is selected from at least one of argon and nitrogen.

[0015] Optionally, the calcination parameters are: heating rate 3-6°C / min, insulation temperature 550-600°C, and insulation time 2-3h.

[0016] Optionally, the mass ratio of the fluoride salt to the precursor is (0.05-0.5):1.

[0017] Optionally, the mass ratio of the fluoride salt to the precursor is 0.1:1.

[0018] On the other hand, the present invention also provides a highly crystalline carbon nitride nanomaterial, which is prepared according to the above-mentioned method for preparing the highly crystalline carbon nitride nanomaterial.

[0019] The invention also discloses the application of the above-mentioned high-crystalline carbon nitride nanomaterial as a photocatalyst in a water decomposition reaction.

[0020] Beneficial effects:

[0021] The method for preparing the highly crystalline carbon nitride nanomaterial of the present invention directly mixes the precursor and the fluoride salt evenly and then calcines them. Only a small amount of fluoride salt and a relatively low calcination temperature are required to prepare the highly crystalline carbon nitride nanomaterial. The preparation process is simple, the preparation cost is reduced, and energy waste is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.

[0023] Figure 1 It is a comparison diagram of the material structures obtained by comparative examples 1-3 and embodiment 1;

[0024] Figure 2 It is a comparison diagram of the material structures obtained in Comparative Example 4 and Example 1;

[0025] Figure 3 This is a comparison chart of the photocatalytic performance of the materials prepared in Comparative Example 1, Comparative Example 4, Comparative Example 7 and Example 1 in the photodecomposition of water to produce hydrogen experiment. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0028] A method for preparing a highly crystalline carbon nitride nanomaterial.

[0029] The precursor and the fluoride salt are uniformly mixed, calcined, washed and dried to obtain a highly crystalline carbon nitride nanomaterial;

[0030] Wherein, the mass ratio of fluoride salt to precursor is (0.01-1):1;

[0031] The calcination parameters are: heating rate 3-8°C / min, holding temperature 550-650°C, and holding time 2-4h.

[0032] By selecting fluoride salt, the fluoride salt and the precursor can be directly mixed and calcined in a one-step method, and then a high-crystalline carbon nitride nanomaterial can be obtained through simple subsequent treatments such as washing and drying, thereby simplifying the preparation process of high-crystalline carbon nitride nanomaterials.

[0033] At the same time, based on the fluoride salt itself as a synthesis template, the amount of fluoride salt required in the preparation process is reduced, the calcination temperature is lowered, and highly crystalline carbon nitride nanomaterials can be prepared at a lower calcination temperature, which reduces the preparation cost and reduces energy waste.

[0034] The precursor may be a carbon nitride-related precursor. In some embodiments, the precursor is selected from at least one of thiourea, melamine, dicyandiamide, and urea.

[0035] The fluoride salt may be an alkali metal fluoride salt. In some embodiments, the fluoride salt is selected from at least one of NaF, LiF, and KF.

[0036] The calcination operation is preferably carried out under an inert gas atmosphere to prevent the active gas atmosphere from affecting the calcination process; wherein the inert gas is preferably at least one of common argon and nitrogen, for example, the inert gas is argon and the inert gas is nitrogen.

[0037] The calcination parameters may preferably be: heating rate 3-6°C / min, holding temperature 550-600°C, holding time 2-3h.

[0038] According to the selected fluoride salt, the amount of fluoride salt required for the preparation process can be reduced. The mass ratio of fluoride salt to precursor is preferably (0.01-0.5):1. Furthermore, the mass ratio of fluoride salt to precursor can also be preferably (0.05-0.125):1.

[0039] The above-mentioned method for preparing highly crystalline carbon nitride nanomaterials can prepare highly crystalline carbon nitride nanomaterials; specifically, in the method for preparing highly crystalline carbon nitride nanomaterials of the present application, since F enters the structure and changes the chemical environment of the adjacent Na and N in the heptazine ring, the material is more likely to form a highly crystalline polyheptazine imide structure, i.e., a PHI structure. The highly crystalline carbon nitride nanomaterial has good photocatalytic effect and can be used as a photocatalyst in water decomposition reactions.

[0040] Example 1, a highly crystalline carbon nitride nanomaterial, the preparation method is as follows: NaF and thiourea are thoroughly mixed and ground in a mass ratio of 0.1:1, and the obtained uniform mixture is placed in a porcelain boat and sealed with a lid; then the sealed porcelain boat is placed in a tubular furnace, and calcined to 550°C at a heating rate of 5°C / min in an inert gas atmosphere (argon or nitrogen), and maintained at 550°C for 2 hours, and then naturally cooled; the cooled sample is thoroughly washed with distilled water, filtered and separated to obtain a solid, and dried at 60°C for 12 hours to obtain a highly crystalline carbon nitride nanomaterial.

[0041] Example 2, a highly crystalline carbon nitride nanomaterial, the preparation method is as follows: LiF and melamine are fully mixed and ground in a mass ratio of 0.3:1, and the obtained uniform mixture is placed in a porcelain boat and sealed with a lid; then the sealed porcelain boat is placed in a tubular furnace, and calcined to 580°C at a heating rate of 3°C / min in an inert gas atmosphere (argon or nitrogen), and maintained at 580°C for 2 hours, and then naturally cooled; the cooled sample is fully washed with distilled water, filtered and separated to obtain a solid, and dried at 80°C for 12 hours to obtain a highly crystalline carbon nitride nanomaterial.

[0042] Example 3, a highly crystalline carbon nitride nanomaterial, the preparation method is as follows: KF and thiourea are fully mixed and ground in a mass ratio of 0.1:1, and the obtained uniform mixture is placed in a porcelain boat and sealed with a lid; then the sealed porcelain boat is placed in a tubular furnace, and calcined to 560°C at a heating rate of 6°C / min in an inert gas atmosphere (argon or nitrogen), and maintained at 560°C for 3 hours, and then naturally cooled; the cooled sample is fully washed with distilled water, filtered and separated to obtain a solid, and dried at 70°C for 12 hours to obtain a highly crystalline carbon nitride nanomaterial.

[0043] Example 4, a highly crystalline carbon nitride nanomaterial, is prepared as follows: NaF and urea are thoroughly mixed and ground in a mass ratio of 0.01:1, and the resulting uniform mixture is placed in a porcelain boat and sealed with a lid; the sealed porcelain boat is then placed in a tubular furnace, and calcined to 550°C at a heating rate of 10°C / min in an inert gas atmosphere (argon or nitrogen), and maintained at 550°C for 2 hours, followed by natural cooling; the cooled sample is thoroughly washed with distilled water, the solid is separated by filtration, and dried at 50°C for 12 hours to obtain a highly crystalline carbon nitride nanomaterial.

[0044] Example 5, a highly crystalline carbon nitride nanomaterial, the preparation method is as follows: NaF and dicyandiamide are thoroughly mixed and ground in a mass ratio of 0.3:1, and the obtained uniform mixture is placed in a porcelain boat and sealed with a lid; the sealed porcelain boat is then placed in a tubular furnace, and calcined to 600°C at a heating rate of 5°C / min in an inert gas atmosphere (argon or nitrogen), and maintained at 600°C for 2 hours, and then naturally cooled; the cooled sample is thoroughly washed with distilled water, filtered and separated to obtain a solid, and dried at 60°C for 12 hours to obtain a highly crystalline carbon nitride nanomaterial.

[0045] The highly crystalline carbon nitride nanomaterials prepared in Examples 1-5 all have similar highly crystalline structures, such as Figure 1 TCNF0.1(550) in.

[0046] At the same time, set a comparison ratio.

[0047] Comparative Example 1 is different from Example 1 only in that NaF is replaced by NaCl to obtain a carbon nitride material; the carbon nitride material here is different from the highly crystalline carbon nitride nanomaterial obtained in Example 1 and does not have the same highly crystalline structure.

[0048] Comparative Example 2 is different from Example 1 only in that NaF is replaced by NaBr to obtain a carbon nitride material; the carbon nitride material here is different from the highly crystalline carbon nitride nanomaterial obtained in Example 1 and does not have the same highly crystalline structure.

[0049] Comparative Example 3 is different from Example 1 only in that NaF is replaced by NaI to obtain a carbon nitride material; the carbon nitride material here is different from the highly crystalline carbon nitride nanomaterial obtained in Example 1 and does not have the same highly crystalline structure.

[0050] Comparative Example 4 is different from Example 1 only in that NaF is replaced by NaCl. In order to obtain a carbon nitride material with a structure similar to that of the highly crystalline carbon nitride nanomaterial in Example 1, the amount of salt and the sintering parameters are adjusted. The mass ratio of NaCl to thiourea is 2:1, and the holding temperature in the sintering parameters is 600°C.

[0051] Comparative Example 5 is a method for preparing a highly crystalline carbon nitride nanomaterial in the prior art, as follows: NaCl and melamine are fully mixed and ground at a mass ratio of 5:1, and the obtained uniform mixture is placed in a porcelain boat and sealed with a lid; then the sealed porcelain boat is placed in a tube furnace, and calcined to 650°C at a heating rate of 5°C / min in an inert gas atmosphere (argon or nitrogen), and maintained at 650°C for 2 hours, and then naturally cooled; the cooled sample is fully washed with distilled water, filtered and separated to obtain a solid, and dried at 60°C for 12 hours to obtain a highly crystalline carbon nitride nanomaterial. Compared with Example 1, this comparative example requires the addition of a large amount of salt and a higher calcination temperature.

[0052] Comparative Example 6 is a method for preparing a highly crystalline carbon nitride nanomaterial in the prior art, as follows: 10 g of melamine is calcined at 550° C. for 4 hours, ground and washed with deionized water, and dried at 60° C. for 12 hours to obtain polymerized carbon nitride (PCN); PCN is dissolved in concentrated sulfuric acid, stirred at 100° C., and after natural cooling, 500 ml of deionized water is added dropwise, and the pH is adjusted to 7.0 with concentrated ammonia, and the solid is washed, filtered and collected to obtain a solid, and the solid is placed in a tubular furnace, calcined at 570° C. for 6 hours under inert gas, the product is ground, and then washed with water to obtain an intermediate product; the intermediate product is ultrasonically dispersed in a NaCl solution, evaporated at 90° C., and dried for 12 hours, and the product is fully washed with water, filtered and dried to obtain a highly crystalline carbon nitride nanomaterial.

[0053] Comparative Example 7 is different from Example 1 in that no alkaline salt is added, and thiourea is only placed in a tubular furnace and heated to 550° C. at a heating rate of 5° C. / min using an inert atmosphere, and calcined for 2 hours.

[0054] Compared with Example 1, this comparative example has a complicated preparation process and a long calcination time, which increases the preparation cost and causes energy waste.

[0055] The materials obtained in Comparative Examples 1-4 and Example 1 were subjected to X-ray diffraction, and the comparison diagrams obtained were as follows: Figure 1 and Figure 2 . Figure 1 This is the XRD test result diagram, the ordinate represents the intensity after diffraction, and the abscissa represents twice the incident angle (in TCNX0.1(550), X=F, Cl, Br, I, which means that NaF, NaCl, NaBr, NaI are calcined with thiourea at a mass ratio of 0.1:1 at 550℃ for 2 hours to obtain the product). Figure 2 This is the XRD test result diagram, the ordinate represents the intensity after diffraction, and the abscissa represents twice the incident angle (TCNF0.1 (550) represents the product obtained by calcining NaF with thiourea at a mass ratio of 0.1:1 at 550°C for 2 hours; TCNCl2 (600) represents the product obtained by calcining NaCl with thiourea at a mass ratio of 2:1 at 600°C for 2 hours).

[0056] In the graph obtained by X-ray diffraction of the material obtained in Example 1, a new peak appears at about 8°, indicating that a highly ordered repetitive structure appears in the two-dimensional layer plane in its structure; in addition, the peak at about 27° is still retained in the spectrum, representing the interlayer stacking of the heptazine ring layered structure; in addition to these two specific peaks, diffraction peaks also appear near 14°, 21°, 26° and 37° in the spectrum of the obtained material, which correspond to the (-210), (-320) and (-530) crystal planes of the PHI structure, respectively. Therefore, the structure with the above-mentioned specific X-ray diffraction peaks is the highly crystalline structure of the present application.

[0057] Among them, the comparison diagram of the material structure obtained by comparative examples 1-3 and embodiment 1 is as follows: Figure 1 As shown, the materials obtained in Comparative Examples 1-3 do not have a high crystalline structure. Specifically, in the figure, TCNF0.1 (550) is a high crystalline carbon nitride nanomaterial obtained in Example 1, TCNC I 0.1 (550) is a carbon nitride material obtained in Comparative Example 1, TCNBr0.1 (550) is a carbon nitride material obtained in Comparative Example 2, and TCN I 0.1 (550) is a carbon nitride material obtained in Comparative Example 3.

[0058] The comparison diagram of the material structure obtained by comparative example 4 and embodiment 1 is as follows: Figure 2 As shown, the material prepared in Comparative Example 4 has a similar high crystalline structure to the material prepared in Example 1. In the figure, TCNF0.1 (550) is the high crystalline carbon nitride nanomaterial prepared in Example 1, TCNC I 2 (600) is the carbon nitride material prepared in Comparative Example 4, and TCN (550) is the carbon nitride material prepared in Comparative Example 7.

[0059] The materials prepared in Comparative Example 1, Comparative Example 4, Comparative Example 7 and Example 1 were used as photocatalysts in the experiment of photodecomposing water to produce hydrogen. The test results obtained are as follows: Figure 3 shown. Figure 3 This is a comparison chart of photocatalytic hydrogen production performance. The ordinate represents the amount of hydrogen produced, and the abscissa represents the time of the photocatalytic reaction.

[0060] The photocatalytic hydrogen production experiment of water decomposition is as follows: 50 mg of photocatalyst (i.e., the materials prepared in Comparative Example 1, Comparative Example 4, Comparative Example 7 and Example 1 are respectively used as photocatalysts) is ultrasonically uniformly dispersed in 50 mL of reaction solution, the solution contains 10 mL of triethanolamine as a sacrificial agent and 40 mL of deionized water, and 3 wt% (relative to the mass of the photocatalyst) of Pt is added as a co-catalyst. After the system is completely degassed, the reaction is irradiated with a 300W xenon lamp (CEAUL I GHT CEL-HXF300, Beijing Zhongjiao Jinyuan) and a 400nm filter for photocatalytic reaction. The photocatalytic hydrogen production is measured using an online gas chromatograph (GC 2014C, TCD detector, Ar as carrier gas, 55 molecular sieve column, SH I MADZU).

[0061] As can be seen from the figure, both Example 1 and Comparative Example 4 produced highly crystalline carbon nitride nanomaterials, and therefore also had good photocatalytic properties, and could be used as photocatalysts for long-term and stable applications in photocatalytic water decomposition and hydrogen production experiments; the materials produced in Comparative Examples 1 and 7 did not have good photocatalytic properties.

[0062] The method for preparing the highly crystalline carbon nitride nanomaterial of the present invention directly mixes the precursor and the fluoride salt evenly and then calcines them. Only a small amount of fluoride salt and a relatively low calcination temperature are required to prepare the highly crystalline carbon nitride nanomaterial. The preparation process is simple, the preparation cost is reduced, and energy waste is reduced.

[0063] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a highly crystalline carbon nitride nanomaterial, characterized in that: The precursor and the fluoride salt are uniformly mixed, calcined, washed and dried to obtain a highly crystalline carbon nitride nanomaterial; The mass ratio of the fluoride salt to the precursor is (0.1-1):1; The calcination parameters are: heating rate 3-8°C / min, holding temperature 550-650°C, holding time 2-4h; The precursor is selected from at least one of thiourea, melamine, dicyandiamide and urea; The fluoride salt is selected from at least one of NaF, LiF, and KF; The calcination is carried out in an inert gas atmosphere, wherein the inert gas is selected from at least one of argon and nitrogen. The high-crystalline carbon nitride nanomaterial has a polyheptazine imide structure.

2. The method for preparing a highly crystalline carbon nitride nanomaterial according to claim 1, characterized in that: The drying parameters are: drying temperature 50-80°C.

3. The method for preparing a highly crystalline carbon nitride nanomaterial according to claim 1, characterized in that: The calcination parameters are: heating rate 3-6°C / min, insulation temperature 550-600°C, and insulation time 2-3h.

4. The method for preparing a highly crystalline carbon nitride nanomaterial according to claim 1, characterized in that: The mass ratio of the fluoride salt to the precursor is (0.1-0.5):

1.

5. The method for preparing a highly crystalline carbon nitride nanomaterial according to claim 1, characterized in that: The mass ratio of the fluoride salt to the precursor is 0.1:

1.

6. A highly crystalline carbon nitride nanomaterial, characterized in that: The highly crystalline carbon nitride nanomaterial is prepared according to the method for preparing the highly crystalline carbon nitride nanomaterial according to any one of claims 1 to 5.

7. Use of the highly crystalline carbon nitride nanomaterial according to claim 6 as a photocatalyst in a water decomposition reaction.